2016
DOI: 10.1007/s10495-016-1299-1
|View full text |Cite
|
Sign up to set email alerts
|

MG132 plus apoptosis antigen-1 (APO-1) antibody cooperate to restore p53 activity inducing autophagy and p53-dependent apoptosis in HPV16 E6-expressing keratinocytes

Abstract: The E6 oncoprotein can interfere with the ability of infected cells to undergo programmed cell death through the proteolytic degradation of proapoptotic proteins such as p53, employing the proteasome pathway. Therefore, inactivation of the proteasome through MG132 should restore the activity of several proapoptotic proteins. We investigated whether in HPV16 E6-expressing keratinocytes (KE6 cells), the restoration of p53 levels mediated by MG132 and/or activation of the CD95 pathway through apoptosis antigen-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…It has been suggested that there is crosstalk between the lysosomal and the proteasomal degradation systems (42,43). For example, proteasomal inhibitors induce compensatory actions to cause autophagy and lysosomal degradation (44)(45)(46). On the other hand, lysosomal inhibition was found to increase or reduce proteasomal activity (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there is crosstalk between the lysosomal and the proteasomal degradation systems (42,43). For example, proteasomal inhibitors induce compensatory actions to cause autophagy and lysosomal degradation (44)(45)(46). On the other hand, lysosomal inhibition was found to increase or reduce proteasomal activity (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome inhibition can induce autophagy via the metabolic stabilization of the transcriptional factor p53 ( Gu et al, 2014 ; Lagunas-Martinez et al, 2017 ). Upon accumulation, the nuclear subpopulation of p53 acts as a transcription factor for autophagy housekeeping genes such as damage-regulated autophagy modifier (DRAM) ( Mrschtik et al, 2015 ; Zhang et al, 2013 ).…”
Section: Crosstalk and Interplay Between The Ups And Autophagymentioning
confidence: 99%
“…Huwe1 is involved in the ubiquitination and degradation of multiple proteins, including P53 (19). Proteasome inhibition in neurons has been shown to induce autophagy via the metabolic stabilization of the transcription factor P53 (9,61,74). recently, it has been revealed that apoptosis signaling exhibits substantial molecular crosstalk with the uPS, as well as autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…However, accumulating evidence has revealed crosstalk between the two degradation pathways (6,7). Previous studies investigating this crosstalk have focused on the compensatory and complementary relationship between autophagy and the uPS (7)(8)(9). it has been shown that uPS dysfunction can activate autophagy in vitro in cell culture and in vivo in animal models via the direct or indirect modulation of proteins associated with cell survival and death (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%